Development and Validation of Stability-Indicating RP-HPLC method for the simultaneous estimation of Olanzapine and Samidorphan in pure API and tablet dosage form in accordance with ICH guidelines (Journal of Pharmaceutical Negative Results, 2022)
The objective of this study is to evaluate Olanzapine and Samidorphan in bulk and tablet dose forms simultaneously.Materials and procedures: On an Xterra (4.6 x 150mm, 5 m) analytical column, the separation was conducted using a mobile phase of 40% buffer (Ortho phosphoric Acid): 60% methanol. The eluents were discovered using a UV detector at 220.0 nm.Results: Olanzapine and Samidorphan were separated at 3.124 and 4.270 minutes, respectively, under ideal conditions. Samidorphan had a detection limit of 0.21 g/mL while Olanzapine had a detection limit of 0.20 g/mL. Olanzapine had a recovery rate of 100.34 percent compared to Samidorphan's percentage mean recovery of 100.01 percent.Conclusion: In each stressful scenario, the proportion of degradation was found to be incredibly low. It was discovered that under optimum conditions, all of them could be determined simultaneously in bulk and marketing dose form.